2016
DOI: 10.1038/srep23019
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical outcome in thoracic ossification of the ligamentum flavum: focusing on the quantitative signal intensity

Abstract: The association between intramedullary increased signal intensity (ISI) on T2-weighted magnetic resonance imaging (MRI) and surgical outcome in thoracic ossification of the ligamentum flavum (OLF) remains controversial. We aimed to determine the impact of signal change ratio (SCR) on thoracic OLF surgical outcomes. We retrospectively reviewed 96 cases of thoracic OLF surgery and investigated myelopathy severity, symptom duration, MRI and computed tomographic findings, surgical technique and postoperative recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…With recent developments and advances in MRI techniques and software, we can quantify various signal intensities of the spinal cord using ROIs in these patients. Zhang et al [ 18 ] reported that preoperative SIR on T2WI of MRI could be potentially useful for the prediction of surgical outcomes in patients with thoracic OLF. Results of the present study corresponded with the results of an earlier study, which reported low SIR as a prognostic factor correlated with high JOA RR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With recent developments and advances in MRI techniques and software, we can quantify various signal intensities of the spinal cord using ROIs in these patients. Zhang et al [ 18 ] reported that preoperative SIR on T2WI of MRI could be potentially useful for the prediction of surgical outcomes in patients with thoracic OLF. Results of the present study corresponded with the results of an earlier study, which reported low SIR as a prognostic factor correlated with high JOA RR.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the present study corresponded with the results of an earlier study, which reported low SIR as a prognostic factor correlated with high JOA RR. Furthermore, 2 previous studies reported that patients with preoperative SIR greater than or equal to 1.54 or 1.55 are likely to experience poor postoperative recovery [ 12 , 18 ]. In accordance with previous studies [ 12 , 18 ], mean SIR (1.41±0.23) was higher in the poor RR group than (1.16±0.17) in the good RR group (p=0.009) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1), indicating that the spinal cord is in the condition of ischemia, and postoperative ND may occur due to the ischemia reperfusion. [21] As Zhang et al [22] noted that patients with preoperative signal change ratio (SCR) ≥1.54 can experience poor postoperative recovery, Li et al [23] demonstrated that intramedullary signal change on T 2 WI and preoperative severity of myelopathy were confirmed and significantly correlated with the surgical outcome. Second, for patients suffering from both ventral and dorsal compression to the dural mater, the spinal cord is vulnerable, and mild traction or only slight vibration may cause severe paralysis at the procedure of extirpation of the OPLL through 1-stage posterior approach.…”
Section: Discussionmentioning
confidence: 99%